Performing economy differently: Exploring economic personhood and local economic diversity - McKay, Deirdre (The Australian Journal of Anthropology, 2009)
Many popular conceptions of economy now delimit what counts as the ‘real’ economy by capitalist enterprises, market transactions and wage labour. Anthropologists describe such ideas of economy as abstract, dis-embedded (Polanyi 1957a, b) or virtual (Carrier and Miller 1998), arguing that these conceptions are not adequate to the empirical realities of lived experience. Beyond anthropology, there is a growing literature that theorises the ways academic accounts have themselves brought a dis-embedded or virtual version of economy into being (Mitchell 2002, 2008; Callon 2005; Callon and Caliskan 2005; Latour 2005; Gibson-Graham 2006). Scholars advocating a performative approach argue that academic notions of economy are not simply descriptive of empirical realities, but actively shape those realities, giving form to the ways that a ‘real’ economy emerges from particular socio-cultural fields. In the context of applied development anthropology, a performative reading of economy offers a helpful platform for applied research directed towards diversifying local economic understandings and practices. This paper explores the implications of performing economy differently through reflections on an action research project undertaken in the Philippines. Here, a performative approach recreated economy as a space of decision that demands active, ethical choices (Gibson-Graham 2006) and supported relational, rather than individuated, models of economic personhood.
Anthropology
Keywords: action research; disembeddedness; economic anthropology; performative approach

The Athenian Economy in Light of the Welfare State: Karl Polanyi's Work in Perspective - Wjuniski, Bernardo Stuhlberger; Fernández, Ramón García (Journal of Economic Issues (Taylor & Francis Ltd), 2009)
Karl Polanyi considered that the relationship between the markets and their societies was a central feature of any social order. He studied what he called "ancient societies," to compare them with his own times, in an effort to understand that subject This paper aims to show, following Polanyi's work on Classical Greece, that it is possible to make a clear analogy between the Athenian state and economy with the modern Welfare State. First, we present Polanyi's study of the early Athenian economy, focusing on the coexistence of a kind of state economic planning and a market Second, we show how this relates to Polanyi's emphasis in the comparison of different societies and times. Third, we characterize the contemporary Welfare State to make an analogy between these two forms of economic organization. We conclude by underlining the relevance of this analogy in understanding the societies of today.
Economics; Anthropology
Keywords: Athenian supremacy; Greece; 479-431 B.C.; Athens (Greece) - history; Greece; Polis (the Greek word); classical Greek economy; economic anthropology; economic policy; embeddedness; equity; history of economics - to 1800; imperialism; markets - social aspects; money; social order; welfare state

Market and Society: The Great Transformation Today - Hann, Chris; Hart, Keith (Cambridge University Press, 2009)
Karl Polanyi's 1944 book, The Great Transformation, offered a radical critique of how the market system has affected society and humanity since the industrial revolution. This volume brings together contributions from distinguished scholars in economic anthropology, sociology and political economy to consider Polanyi's theories in the light of circumstances today, when the relationship between market and society has again become a focus of intense political and scientific debate. It demonstrates the relevance of Polanyi's ideas to various theoretical traditions in the social sciences and provides perspectives on topics such as money, risk, work and the family. The case studies present materials from around the world, including Britain, China, India, Jamaica and Nigeria. Like Polanyi's original work, the critical engagement of these essays will be of interest to a wide readership.
Anthropology; History
Keywords: anthropology - general; business & economics; economic history; economic theory; sociology - general

Exchange networks and free shops in Berlin: gifts and commodities in ‘alternative’ consumption experiences - Sabaté Muriel, Irene (Etnográfica. Revista do Centro em Rede de Investigação em Antropologia, 2009)
This paper is based on an ethnography of ‘alternative’ consumption practices in the inner city of the former East Berlin. Non-monetary exchange networks (Tauschringe) and ‘free shops’ (Umsonstläden) have been examined. In Umsonstläden, the contemporary ideology of the ‘pure’ gift (Parry 1986; Carrier 1995) is at play: objects are freely given and totally alienated from their owners. In turn, Tauschringe sometimes induce gift-giving practices entailing mutual obligation, as a result of frequent exchanges which bring participants socially closer. The ethnographic material I present challenges the suitability of a conceptual gift / commodity divide to examine these experiences, provided that different modalities of gift-giving are articulated with commoditisation trends. Considering this complexity, I propose a re-examination of the role of the gift in ‘alternative’ consumption practices promoted by social movements in Berlin., O artigo baseia-se numa etnografia de práticas de consumo “alternativas” nos bairros centrais da antiga Berlim-Leste. São aqui analisadas as redes de intercâmbio não monetário (Tauschringe) e as “lojas gratuitas” (Umsonstläden). As Umsonstläden são enquadradas pela ideologia contemporânea da dádiva “pura” (Parry 1986; Carrier 1995): os objectos são dados gratuitamente e totalmente alienados dos seus possuidores. Já as Tauschringe, por seu lado, induzem por vezes práticas de oferta que implicam obrigações mútuas, como consequência de trocas frequentes que aproximam socialmente os participantes. O material etnográfico apresentado põe em causa a adequação do binómio dádiva / mercadoria à análise dessas experiências, na medida em que diferentes modalidades de oferta se conjugam com tendências para a mercadorização. Face a essa complexidade, o artigo propõe uma revisão da análise do papel da dádiva em práticas de consumo “alternativas” promovidas pelos movimentos sociais em Berlim.
Anthropology
Keywords: Berlin; consumption; economic anthropology; embeddedness; exchange networks; fallacy of the market; free shops; gifts/commodities; social economy; social movements

Economics, Anthropological Models and the Ancient Near East - Warburton, David A. (Anthropology of the Middle East, 2009)
This article discusses the evidence of markets in the Ancient Near East. The major points are (1) the shortcomings of the misguided application of the Polanyi model and (2) the ensuing implications of the failure to integrate economic history into modern economic theory. The analysis concentrates on Ancient Egypt, as it presents the most significant problem for economic history and theoretical modelling. Detailed criticism of the means by which the Polanyi model is upheld is coordinated with an argument in favour of recognising the importance of markets. The argument is that these markets are relevant both to long-term economic history and to modern economic theory – and that this must lead to a new debate about ancient and modern economies.
Anthropology
Keywords: Egypt; Middle East; ancient civilization; anthropology; economic history; economic theory; economics; markets; neo-classical synthesis; technology